Method affinity: between semiotics and semio-aesthetics - Finocchi, Riccardo (E|C, 2020)
I ask myself a question: can we talk about a semiotic method? that is, can we speak of a semiotic method using the singular preposition "a"? Could it not, however, be correct and acceptable to affirm that semiotics is crossed by methods?